World economy : a textbook in international economics - Williamson, John.; Milner, Chris (New Yark, 1991)
This is a revised and updated version of John Williamson's successful textbook "The Open Economy". The major change has been a substantial extension of the section on trade theory both to cover previous material in greater depth and to cover new developments in strategic trade theory. The coverage of trade policy is also extended to cover both the "old protectionism" (tariffs, etc) and the "new protectionism" embodied in concepts such as voluntary export restraint agreements. There have also been new developments on the monetary aspects of international exchange and payments since the first edition was published. All of these topics are also fully updated and extended. In addition, all of the institutional material has been updated to reflect the events of the 1980s and thus includes coverage of the Uruguay Round of GATT multilateral trade negotiations and the international implications of environmental issues. This book now represents a complete, rounded and accessible text for all students of international economics at intermediate and advanced levels.
Keywords: International economics